Reconciling VEGF With VPF: The Importance of Increased Vascular Permeability for Stroma Formation in Tumors, Healing Wounds, and Chronic Inflammation - Dvorak, Harold F. (Frontiers in Cell and Developmental Biology, 2021)
It is commonly believed that Vascular Endothelial Growth Factor (VEGF) induces angiogenesis by its direct mitogenic and motogenic actions on vascular endothelial cells. However, these activities are only detected when endothelial cells are cultured at very low (0.1%) serum concentrations and would not be expected to take place at the much higher serum levels found in angiogenic sites in vivo. This conundrum can be solved by recalling VEGF’s original function, that of an extremely potent vascular permeability factor (VPF). In vivo VPF/VEGF renders microvessels permeable such that whole plasma leaks into the tissues where it undergoes clotting by tissue factor that is expressed on tumor and host connective tissue cells to deposit fibrin and generate serum. By providing tissue support and by reprograming the gene expression patterns of cells locally, fibrin and serum can together account for angiogenesis and mature stroma formation. In sum, by increasing vascular permeability, VPF/VEGF triggers the “wound healing response”, setting in motion a fundamental pathophysiological process that induces the mature stroma that is found not only in healing wounds but also in solid tumors and chronic inflammatory diseases. Once initiated by increased vascular permeability, this response may be difficult to impede, perhaps contributing to the limited success of anti-VEGF therapies in treating cancer.